The Application and Reflection of PAD in College English Teaching - Zhang, Jingling; Zheng, Peiwei (International Journal of English Literature and Social Sciences (IJELS), 2019)
PAD is the abbreviated form of presentation, assimilation and discussion, which is "The Original Teaching Mode in China". It is mainly a new teaching method proposed in view of the current situation of the classroom in colleges and universities in China. It can improve the teaching effect by enhancing students' learning initiative. Starting with the connotation of PAD, combining the current situation of College English classes and the author’s experience, this paper analyses the feasibility of PAD in College English teaching and discusses the existing problems. The author believes that the method provides a new model for college English teaching reform, which is innovative and worth further exploration in practice. It is expected to be more widely used in teaching activities at all levels and disciplines.